(untitled) (Journal of Applied Learning and Teaching, 2020)
Higher education is governed by national quality standards with increasing expectations that teaching staff engage in quality assurance processes, including Assurance of Learning (AoL). AoL recommends a teaching team approach to measure student learning outcomes against specific course goals. Appropriate skills and allocated time are essential to support staff to ensure the curriculum is designed to comprehensively address student learning and develop knowledge, skills and desired graduate capabilities. The 360 Quality Pursuit (360QP) approach to AoL is underpinned by a social constructivist approach to knowledge development, designed by a University of Tasmania Community of Practice that evolved into an interinstitutional action research team. 360QP is a six-segment, semi-formal quality enhancement program that can be applied to any educational activity or level of organisation (e.g. unit, course or college). Using a regulatory compliance lens for AoL can adversely constrain the focus of professional development (PD) and limit staff engagement. This paper combines the findings from our scoping review with data collected from five national workshops. Workshop participants were invited to explore the 360QP segments, share case studies and offer their top PD wish list items. This culminated in the identification of 15 conditions that academics believe are required to support AoL.